Performance of lemongrass (Cymbopogon citrates) oil as growth promoter in broiler: Lemongrass oil in broiler diet - Tiwari, MR; Jha, PK; Sah, B; Kunwar, G; Jha, AK (Bangladesh Journal of Animal Science, 2018)
An attempt was taken to study the growth performance of lemongrass oil (Cymbopogon citraturs) as a growth promoter on the broiler production. A total of 180day-old broiler chicks were procured from private hatchery (Shivam Hatchery Birgung, Parsa, Nepal) and were allocated following Completely Randomized Design (CRD) into four treatment groups (each treatment with 3 replications and each replication with 15 birds); T1= control, T2= containing lemongrass oil 200 ml/100 kg feed, T3= containing lemongrass oil 400 ml/100 kg feed and, T4= containing lemongrass oil 600 ml/100 kg feed. The study was carried out for 36 days at Avian Research Unit, Regional Agriculture Research Station, Parwanipur, Bara, Nepal. Concentrate mixture and lemongrass oil were procured from Shakti Feed Industry, Birgung; Herbs Processing Plant of Ministry of Forest and Soil Conservation, Jadibuti, Kathmandu, respectively. Experimental birds were provided ad libitum amount of starter feed from 0 to 21 days and finisher feed from 22 to 36 days. Feed intake was recorded daily and body weight gain was measured in 7 days interval. The study revealed that the cumulative feed intake per bird was found higher in T3 (3443.17g) followed by T4 (3377.33g) and T2 (3354.04g), respectively, and were statistically non-significant among the diet groups. The FCR was highest in T3 (1:1.44 kg) and lowest in T4 (1:1.51 kg), and differed insignificantly among the diet groups. Similarly, the total weight gain of the experimental bird was found to be higher in T3 (2385.13g) followed by T1 (2279.46g) and T2 (2271.86g), respectively. The average daily gain of experimental birds noted higher in T3 (66.25g) followed by T1 and T2 (63.31g) and (63.1g), respectively. The experiment suggested that inclusion of lemongrass oil could be considered as an alternative to antibiotic growth promoter in broiler diet to enhance the production performance. Bang. J. Anim. Sci. 2018. 47 (2): 85-91